Pore length scales and pore surface relaxivity of sandstone determined by internal magnetic fields modulation at 2 MHz NMR - Liu, Huabing; D’Eurydice, Marcel Nogueira; Obruchkov, Sergei; Galvosas, Petrik (Diffusion Fundamentals, 2014)
Pore length scales and pore surface relaxivities of sandstone were studied on a 2 MHz Rock Core Analyzer in this work. To determine the pore length scales of rock cores, high eigenmodes of diffusion equation were detected with optimized encoding periods in the presence of internal magnetic fields B in. The results were confirmed by a 64 MHz NMR system. Furthermore, this methodology was combined with relaxometry measurements , which provides the two-dimensional correlation of pore length with relaxation time and yield information on the surface relaxivity of rock cores. The estimated surface relaxivities were compared with the results from an independent NMR method.